2021
DOI: 10.1155/2021/5516185
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signatures of Human Chronic Atrial Fibrillation in Primary Mitral Regurgitation

Abstract: Objectives. Transcriptomics of atrial fibrillation (AFib) in the setting of chronic primary mitral regurgitation (MR) remains to be characterized. We aimed to compare the gene expression profiles of patients with degenerative MR in AFib and sinus rhythm (SR) for a clearer picture of AFib pathophysiology. Methods. After transcriptomic analysis and bioinformatics ( n = 59 ), diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…Studies have shown that mutations in COLQ can lead to congenital myasthenic syndrome (CMS), which causes cardiac autonomic dysfunction ( 32 , 33 ). Interestingly, Çubukçuoğlu et al ( 34 ) found that the expression of COLQ was higher in degenerative mitral regurgitation patients with AF than in those with SR ( P = 0.003), which is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that mutations in COLQ can lead to congenital myasthenic syndrome (CMS), which causes cardiac autonomic dysfunction ( 32 , 33 ). Interestingly, Çubukçuoğlu et al ( 34 ) found that the expression of COLQ was higher in degenerative mitral regurgitation patients with AF than in those with SR ( P = 0.003), which is consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 93%
“…The mucin subfamily is also known as transient receptor potential channels, is highly expressed in cardiac fibroblasts, and MCOLN3 , a member of the mucin subfamily, plays an important role in the regulation of calcium ion homeostasis ( 33 ). The downregulation of MCOLN3 has been shown to be closely associated with AF related to chronic primary mitral valve closure insufficiency ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The microarray dataset GSE115574 was retrieved from the GEO database. This dataset contained 14 left atrial tissue samples from persistent AF patients [ 19 ]. The expression of all genes in every sample is shown in Figure 1 , and no significant outlier samples were found.…”
Section: Methodsmentioning
confidence: 99%